2020
DOI: 10.1038/s41467-020-18519-0
|View full text |Cite
|
Sign up to set email alerts
|

IRF1-mediated downregulation of PGC1α contributes to cardiorenal syndrome type 4

Abstract: Cardiorenal syndrome type 4 (CRS4) is a common complication of chronic kidney disease (CKD), but the pathogenic mechanisms remain elusive. Here we report that morphological and functional changes in myocardial mitochondria are observed in CKD mice, especially decreases in oxidative phosphorylation and fatty acid metabolism. High phosphate (HP), a hallmark of CKD, contributes to myocardial energy metabolism dysfunction by downregulating peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…In accordance with the manufacturer’s instructions, total RNA from the above mentioned 60 tissue samples was extracted using TRIzol Reagent (Invitrogen, United States), and the OD260/OD280 of RNA was detected using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, United States). Only when the OD260/OD280 of RNA was between 1.8 and 2.0, was the RNA used for subsequent reverse transcription with a reverse transcription kit (FSQ-301, Toyobo, Japan) ( Huang et al, 2020 ). Reverse transcription was performed in a 10-μL reaction volume using the Applied Biosystems 7500 Real-time PCR system with SYBR Green Real-time PCR Master Mix (QPK-201, Toyobo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the manufacturer’s instructions, total RNA from the above mentioned 60 tissue samples was extracted using TRIzol Reagent (Invitrogen, United States), and the OD260/OD280 of RNA was detected using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, United States). Only when the OD260/OD280 of RNA was between 1.8 and 2.0, was the RNA used for subsequent reverse transcription with a reverse transcription kit (FSQ-301, Toyobo, Japan) ( Huang et al, 2020 ). Reverse transcription was performed in a 10-μL reaction volume using the Applied Biosystems 7500 Real-time PCR system with SYBR Green Real-time PCR Master Mix (QPK-201, Toyobo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Traditional risk factors [ 49 ], unfortunately, are insufficient to completely explain the high prevalence of cardiac death in children from 0 to 19 years old on dialysis or transplanted [ 50 , 51 , 52 ]. In these patients, the complications leading to death may be linked also to uremia-related risk factors [ 6 ]. A cross-sectional investigation of all pediatric maintenance hemodialysis patients (aged 0.7–18 years, n = 656) revealed that 38% have anemia, 63% have serum phosphorus >5.5 mg/dL, and 55% have a calcium–phosphorus product >55 mg 2 /dL 2 [ 53 ].…”
Section: Crs Typementioning
confidence: 99%
“…Huang et al recently demonstrated in an experimental study that a uremic molecule, known as high phosphate (HP), contributes to CKD-associated HF [ 6 ]. HP is crucial in the impairment of myocardial energy metabolism function by inducing alterations in the transcriptional factor interferon regulatory factor 1 (IRF1)–peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC1a) signaling pathway.…”
Section: Crs Typementioning
confidence: 99%
See 2 more Smart Citations